2014
DOI: 10.5194/acpd-14-26939-2014
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polycyclic aromatic hydrocarbons, polychlorinated biphenyls, and chlorinated pesticides in background air in central Europe – investigating parameters affecting wet scavenging of polycyclic aromatic hydrocarbons

Abstract: Abstract. Concentrations of polycyclic aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and chlorinated pesticides (CPs) were measured in air and precipitation at a background site in central Europe. Σ PAH concentrations in air and rainwater ranged from 0.7 to 327.9 ng m−3 and below analytical method detection limit (< MDL) to 2.1 × 103 ng L−1. The concentrations of PCBs and CPs in rainwater were < MDL. Σ PCB and Σ CP concentrations in air ranged from < MDL to 44.6 and < MDL to 351.7… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Very high levels of PCBs were also found in soil samples from northern Vietnam, with concentration ranges of 14,500–130,000 ng/kg [ 36 ]. In turn, airborne PCBs levels in Mataró were similar to those previously reported in other industrial and urban areas worldwide [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…Very high levels of PCBs were also found in soil samples from northern Vietnam, with concentration ranges of 14,500–130,000 ng/kg [ 36 ]. In turn, airborne PCBs levels in Mataró were similar to those previously reported in other industrial and urban areas worldwide [ 37 , 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…The air temperature in winter 2015/2016 was the second highest in the studied period 2006-2017 (Table S14) resulting in a higher percentage of semivolatile OPAHs in the gas phase. The higher share of OPAHs in the gas phase leads to a lower amount of deposited pollutants, since wet and dry deposition of gaseous substances is much less efficient than of substances in the particulate fraction (Bidleman, 1988;Shahpoury et al, 2015;Š krdlíková et al, 2011). Elevated concentrations in air of the examined OPAHs can be confirmed by data from Nežiková et al (2021).…”
Section: Composition Pattern Of Opahsmentioning
confidence: 78%
“…Thus, we hypothesize that the difference in contribution is caused by the gas-particle partitioning of these low MW OPAHs, which have a small particulate fraction, even in winter (particulate fraction of all seasons B 0.01 and 0.04 ± 0.05 for DBF and 9-OFLN, respectively; Nežiková et al, 2021). Since the gaseous lipophilic pollutants are not efficiently deposited by wet and dry deposition (Bidleman, 1988;Shahpoury et al, 2015;Š krdlíková et al, 2011), their contribution in air is much higher than in soil. The same is found for the 3-ring PAHs FLN and PHE (Fig.…”
Section: Composition Pattern Of Opahsmentioning
confidence: 99%
See 1 more Smart Citation
“…included in a national program (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) showed annual mean BaP levels of 0.25 ng m -3 (Meijer et al 2008), while almost 10 times higher annual PM-bound BaP concentrations were identified in the mainland of China, including large cities such as Beijing, Chengdu, Dalian, Gangzhou, Nanchang, Shihezi, Kumning, Lanzhou, Lhasa, Harbin, Xi'an (Ma et al, 2018) and Korea (Park et al, 2002). Recent long-term measurements at a European background site in Košetnice (Czech Republic) showed a large range for BaP concentrations in total particulate matter (<LOQ -9.1 ng m -3 , Shahpoury et al, 2015), with a mean level of 0.4 ng m -3 , which was almost 4.5 times lower than in the city of Poznań, central Poland (Siudek, 2018). The mean annual PM2.5-BaP deposition flux in Gdynia amounted to 294 ng m -2 , which was much lower than that observed in Izmit Bay (1500 ng m -2 month -1 , Pekey et al, 2007), Cardiff and Manchester (6600 and 9000 ng m -2 month -1 , respectively, Hallsal et al, 1997).…”
Section: Accepted Manuscriptmentioning
confidence: 99%